Online Education Posters As A Media For Understanding The New Variant of Covid-19 and Its Prevention - Rozana Alfi Sania; Dwi Rachmawati; Salsabila Fabianca Alsaid; Maftuchah Rochmanti (Journal of Community Medicine and Public Health Research, 2023)
The case of Covid-19 in Indonesia has a lot of issues due to the latest variant, namely the delta variant, which is very dangerous and easily transmitted. The highest number of hoaxes and lowest interest in reading among Indonesian people had made Indonesia at the second-lowest level of world literacy. These online education posters are one of the community's innovative educational media, as stated in program number 4 of Sustainable Development Goals (SDGs), the Quality Education. This research described the effectiveness of educational posters as a media for Instagram users to understand the new variant of Covid-19. Educational posters are uploaded online, and the target audience is the general public through Instagram's feed and story features. They were then evaluated using quizzes in Instagram stories. The data obtained were analyzed descriptively and quantitatively. As many as 407 Instagram social media users participated in this research. There were 336 participants (82.5%) with a score more than or equal to 71 (range of values 0-100), where they could answer a minimum of 5 questions correctly. This study showed that online education posters were considered effective in educating the majority of the community about the new variant of Covid-19 and its prevention.